The relationship between mindfulness and metacognitive beliefs with emotional intelligence - Koohneshin Taromi, Farahnaz; Parandin, Shima (Social Determinants of Health, 2017)
Background: Emotional intelligence is a set of teachable abilities and skills that prepare people for the sustainability and success in life. The purpose of the present study was to predict the emotional intelligence based on metacognitive beliefs and mindfulness beliefs in the students. Methods: A total of 341 students were selected from Islamic Azad University, West Islamabad branch, using random cluster sampling from different university majors at the faculty of Social Sciences. They responded to Bar-Anne’s Emotional Intelligence Questionnaire, the short form of the Wells Meta-Cognition Questionnaire, and Baer et al. Mindfulness Questionnaire. Data were analyzed using Pearson correlation coefficient and stepwise regression. Results: Among the participants 200 (67.5%) were girl students. the age of the participants ranged between18 and 52 years old. Also 254, (78%) had Bachelor’s degree and 87 (21.97%) had Master’s degree. Moreover, 105 (77.33%) were married. The mean (SD) of mindfulness were 107.3 (5.12), meta-cognitive beliefs 47.8 (5.01), and emotional intelligence 85.9 (13.43), respectively. The results of regression analysis showed that metacognitive beliefs were independent predictor of students’ emotional intelligence (P<0.001, F=34.59). Metacognitive beliefs predicted a total of 21% of students’ emotional intelligence. Conclusion: Considering the findings of the present study, it can be stated that more attention should be paid to metacognitive beliefs as an independents predictor of emotional intelligence.